Dampak Kolaborasi Karang Taruna Sebagai Mitra Pemerintah Daerah dalam Pemberdayaan Masyarakat di Kelurahan Jatirasa Kota Bekasi - Rohadi, Gusmantiar Syamsi; Ningsih, Sari; Setyawati, Kiki (WINDRADI: Jurnal Pengabdian Masyarakat, 2025)
This study aims to analyze the impact of collaboration between Karang Taruna, a local youth organization, and the municipal government in community empowerment in Jatirasa Sub-district, Bekasi City. The research employed a qualitative approach through in-depth interviews, field observations, and document analysis. The findings indicate that the collaboration has generated positive contributions to social, economic, and environmental dimensions, particularly by enhancing youth participation, strengthening community-based activities, and facilitating access to empowerment programs. Nevertheless, the study also identifies several challenges that reduce the effectiveness of the collaboration. These include the limited involvement of Karang Taruna in planning processes, high dependency on government support, and programs that do not fully address the specific needs of the local community. Key supporting factors for collaboration include institutional backing, youth enthusiasm, and participatory forums such as local development planning meetings. Conversely, inhibiting factors consist of limited resources, government dominance in policy decisions, and uneven distribution of program benefits. The study emphasizes the need for a more participatory institutional design and capacity-building efforts to strengthen Karang Taruna’s role as an equal partner in local development. The implications of this research provide strategic recommendations for local governments and youth organizations to enhance collaborative quality and achieve sustainable community empowerment.